Structural and geochronological constraints on the evolution of the Juréia Massif, Registro Domain, State of São Paulo, Brazil - Cláudia R. Passarelli (Anais da Academia Brasileira de Ciências, 2007)
The Juréia Massif, southeastern São Paulo State (Brazil), is part of the Registro Domain, limited to the north by theCubatão-Itariri Shear System and to the south by the Serrinha Shear Zone. Mostly composed of migmatitic granitegneissrocks, represents a Paleoproterozoic terrane (1.92.2 Ga) strongly deformed during the Neoproterozoic (750580 Ma). The present tectonic scenario was established at the end of the Neoproterozoic, as a result of collagesassociated with the formation of Western Gondwana. The Ponta da Juréia, our study area within the Juréia Massif,is constituted by paragneisses (garnet-muscovite-biotite gneisses). The monazite U-Pb age of 750 Ma is related to amain regional metamorphic event that reached the high amphibolite facies, recorded in rocks from the Itatins Complexand Cachoeira Sequence as well, which also belongs to the Registro Domain. The paragneissic rocks of this study areaffected by the E-W-trending Serrinha Shear Zone, registering a predominantly dextral movement. Biotite K-Ar agesof 482 ± 12 Ma may represent later movements and reflect the younger ages of reactivation of the major lineamentsand juxtaposition of the tectonic blocks involved.